Institutions and the evolution of capitalism Implications of evolutionary economics - edited by John Groenewegen (Cheltenham Edward Elgar, 1999)
Capitalism is Change'. This famous expression of Joseph Schumpeter was not only characteristic of his time, but is certainly relevant as we enter the twenty-first century. The transition of Eastern Europe and the former Soviet Union, the Asian crisis and European integration all characterise the continuous change of capitalism.
Includes bibliographical references and index.
Keywords: Evolutionary economics; Institutional economics; Capitalism